ANALISIS PROGRAM KAMPUNG KELUARGA BERENCANA (KB) PADA KELURAHAN TALIA, KECAMATAN ABELI KOTA KENDARI - Feriani Feriani; Sartiah Yusran; Ramadhan Tosepu; Adius Kusnan (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2021)
This research is based on the launching of Family Planning in Talia Village. The purpose of this research is to describe and analyze the implementation of the Family Planning Program in Talia village, District Abeli Kendari Municipalities, The method used in this research is descriptive qualitative. The data used are primary and secondary data, where the data sources obtained from informants were selected based on purposive sampling. The data collection techniques using the method of observation, documentation, and interviews then was analyzed the data reduction. The results of this research indicate that generally, the implementation of a family planning program in Talia District has been going well. Only there is one activity that has not been done, the Youth Counseling Center (PIK) Youth. The general objective of this program is still in the process of achieving the program due to the family planning program in the Talia Village started in February 2018. The resources, the quality of inter-organizational relations, and the characteristics of the organization has supported the implementation of family planning programs in the Talia Village.